The little book of sideways markets : how to make money in markets that go nowhere - Katsenelson, Vitaliy N. (Hoboken, N.J. : Wiley, 2011)
"Contrary to popular opinion, markets rarely experience significant periods down; half of the time they do rise but the other half of the time they go nowhere - trading seemingly mindlessly in a range with quick ups and breathtaking downs, only to come back to where they were. These periods last far too long to just buy and hold, since that kind of a strategy leads to 0 returns or worse. What's an investor to do when you have to save for college educations and retirement but the markets are going nowhere? Vitaliy Katsenelson has the answer: a value investing strategy with a focus on when to sell will get you through the whipsaws of sideways markets and coming out well ahead. Vitaliy clearly explains the market cycles and then provides you with a simple strategy that Tevya the Milkman uses to invest that follows three simple rules for quality, growth, and value. Katsenelson also marks the traps and pitfalls that lay in wait so you can avoid them and take a look over the horizon at the oncoming crises in Japan and China. Sideways markets aren't as fun as bull markets but once you understand how to make money in them, much like turning lemons into lemonade, you'll find your portfolio grows nicely even when the market is stalled"--
rua 15/05/13
Loans
Keywords: Stock exchanges; Business cycles; Investments